Membranoproliferative glomerulonephritis in the setting of multicentric angiofollicular lymph node hyperplasia (Castleman's disease) complicated by Evan's syndrome. Issue 6 (3rd May 2010) - Gakiopoulou, Hariklia; Korkolopoulou, Penelope; Paraskevakou, Helen; Marinaki, Smaragdi; Voulgarelis, Michael; Stofas, Anastasios; Lelouda, Maria; Lazaris, Andreas C; Boletis, John; Patsouris, Efstratios
Abstract : Systemic Castleman's disease is a lymphoproliferative disorder with various clinical presentations and incompletely understood aetiology. The authors report on a rare case of the plasma cell variant of Castleman's disease associated with autoimmune haemolytic anaemia and autoimmune thrombocytopenia (Evan's syndrome) and complicated by mixed nephrotic–nephritic syndrome and acute renal failure due to an underlying glomerulopathy with microscopic and immunofluorescence findings suggestive of membranoproliferative glomerulonephritis (MPGN) type I. Immunocomplexed glomerulonephritis is rare in Castleman's disease, while, to the best of our knowledge, constellation of all these autoimmune phenomena is reported for the first time suggesting that apart from the putative role of VEGF and IL-6 in the pathogenesis of the disease, a more generalised immunological disturbance occurs, probably through autoantibodies induced by active polyclonal B cells raised from Castleman's disease tumour.